APPEARANCE OF INPARI IR NUTRI ZINC AND INPARI 32 IN LEBAK SWAMP LAND IN PALEMBANG SOUTH SUMATRA - Suparwoto Suparwoto (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2022)
New superior varieties are one of the innovative technologies that are reliable for increasing rice productivity, both through increasing crop yields and tolerance to biotic and abiotic stresses . Generally, farmers in the Lebak swamp use high-yielding varieties that are self-propagated from year to year, which results in low production. Therefore, in this study, the Inpari IR Nutri Zinc variety was introduced which has advantages compared to other varieties in terms of zinc content, while Inpari 32 is already adaptive in the lebak swamp with a potential yield of 8-9 tons/ha. The purpose of this study was to determine the appearance of Inpari IR Nutri Zinc and Inpari 32 using the legowo row planting system 2:1 in the Lebak swamp. The research was carried out in Sei Selincah Village, Kalidoni Subdistrict, Palembang, South Sumatra, from April to September 2021 with an agro-ecosystem of the middle Lebak swamp. The technology introduced consisted of the Inpari IR Nutri Zinc and Inpari 32 varieties, legowo row planting spacing 2:1 (50x25x12.5 cm) and balanced fertilizer. Observation data included: plant height at harvest, number of productive tillers, panicle length, number of grain/panicle, number of pithy grain/panicle and productivity. Analysis of the financial feasibility of rice farming by calculating gross income or Total Revenue (TR) and net income or Net Revenue (NR). The TR and NR values ​​obtained are then used to measure the financial feasibility of farming using R/C ratio analysis. The results of the study showed that growth and yield components were not significantly different except for panicle length and productivity. The productivity of Inpari IR Nutri Zinc is 6.2 tons gkp/ha and Inpari 32 is 7.0 tons gkp/ha